I’dādu al Kitābu al Mushohib likitābi “ Al Amtsilati Al Tashrifiyyah “ Litarqiyyati Mahāroti Al Kalāmi - Segaf Baharun (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Teaching materials are special materials that contain educational content, and companion books are part of textbooks, not from basic materials, but from auxiliary materials to solve problems in the process of teaching and developing speaking skills, and some of the problems that exist in the learning process, including students. not used to using the right words in conversation, and the need for students to practice after studying for the book al amsilatusrifiah to accustom them to practicing what they have memorized from the book al amsilatusrifiah.             The aims of this study were: 1) To know the process of compiling a companion book to the book al amsilatutasrifiah to improve speaking skills 2) To find out the effectiveness of using the companion book to the book al amsilatutasrifiah to improve speaking skills.             This research approach is a quantitative approach, to obtain values ​​of the effectiveness of using companion books and a qualitative approach, and development research methodology, namely the approach used to develop certain products and test their effectiveness. The data collection methods are interviews, observation, pre and post tests, and questionnaires.             The results of this study are as follows the process of compiling a companion book is: 1- a) Needs analysis b) Problem analysis c) collecting data d) making a product e) product improvement f) product trial g) product improvement product trial h) field trial i) product improvement j) production 2- A companion book to the book of al amsilatu tasrifiah to improve effectively speaking skills with written test results.